Penerapan Teori Humanistik Abraham Maslow Dalam Pembelajaran PAI Untuk Meningkatkan Kesadaran Diri dan Tanggung Jawab Sosial - Elma Fauziyyah; Nurul Latifah; Hasna Nur Lathifah; Mustaqoroh Nurul Izati; Bagus Mahardika (PT. Nawa Edukasi Nusantara, 2026)
This study aims to explore the application of Abraham Maslow’s humanistic theory in the learning process of Islamic Education (PAI) to enhance students' self-awareness and responsibility. Challenges such as moral crises and individualism demand a shift in PAI instructional methods, moving from mere cognitive knowledge transfer to a more humanistic approach. The methodology employed in this study is descriptive qualitative with a library research approach. Data were collected through the documentation of relevant literature and analyzed using content analysis and source triangulation. The results of this study indicate that the application of Maslow's hierarchy of needs in PAI creates a student-centered learning environment, where the fulfillment of basic needs (physiological, safety, and love/belonging) is a prerequisite for achieving self-actualization. The integration of art therapy methods proved effective as a medium for creative expression and strengthening the internalization of religious values and social empathy. Supporting factors include the teacher's role as a facilitator and an inclusive school environment, while hindering factors include a rigid academic orientation and limited teacher pedagogical competence in humanistic approaches. This study concludes that Abraham Maslow's humanistic approach can cultivate a holistic Muslim character through a balance of emotional, spiritual, and social aspects.